The effects of intra-operative amiodarone loading on the systemic inflammatory response syndrome induced by cardiopulmonary bypass - Rahman, Ali; Akbulut, Handan; Bayar, Mustafa Kemal; Ozden, Mehmet; Burma, Oktay; Uysal, Ayhan (Turkish Soc Cardiology, 2009)
Objective: Cardiopulmonary bypass (CPB) leads to systemic inflammatory response syndrome (SIRS). In vitro studies showed that amiodarone blocked cytokine production. The aim of this study was to evaluate the effect of intra-operative amiodarone loading on SIRS. Methods: This prospective randomized study included 24 patients who underwent on-pump coronary artery surgery. The patients were classified into control (n=12) and amiodarone (n=12) groups. Plasma levels of the pro-inflammatory (C-reactive protein - CRP interleukin-6 - IL-6) and the anti-inflammatory markers (interleukin-10 - IL-10) were measured before the induction of anesthesia, 5 minutes after aortic declamping, after protamine administration and 24 hours after the CPB. The myocardial lactate production was calculated before CPB and 5 minutes after aortic declamping. Statistical analyses were performed using Mann-Whitney U, Fischer's exact and ANOVA tests. Results: In both groups, the IL-6 levels significantly increased after declamping (91.18 +/- 16.27 pg/ml and 86.37 +/- 14.66 pg/ml, p<0.01) and reached peak values after infusion of protamine (329.07 +/- 32.24 pg/ml and 354.31 +/- 29.61 pg/ml, p<0.01). The highest values of IL-10 were detected after infusion of protamine in the control and amiodarone groups (265.58 +/- 85.63 pg/ml, p<0.01 and 287.44 +/- 65.26 pg/ml, p<0.01). Amiodarone did not have any significant effect on release of cytokines. The CRP levels were significantly elevated in both groups at 24(th) hour after CPB, but no significant difference was found between the groups. Compared with pre-CPB values, lactate production increased significantly in two groups after aortic declamping. However there was no significant difference between the groups. Conclusions: The results indicate that intraoperative loading of amiodarone, which is used for atrial fibrillation prophylaxis, does not seem to alter inflammatory response during CPB. (Anadolu Kardiyol Derg 2009, 9:318-24)
Keywords: Amiodarone; cardiopulmonary bypass; inflammatory response; C-reactive protein; interleukin; coronary artery surgery